Les articles 8, 9 et 10 de la Charte canadienne des droits et libertés - Choquette, Marie (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
Legal rights protected under sections 8, 9 and 10 of the Canadian Charter of Rights and Freedoms are the subject of this article. Section 8 affords protection against unreasonable search or seizure; there was no similar provision under the Canadian Bill of Rights. Authorized searches and seizures by warrant will be considered unreasonable whenever minimal standards laid down in section 443 of the Criminal Code have not been respected. Furthermore, searches or seizures without warrant will be judged unreasonable if they do not conform to the legal provisions under which they are authorized. Section 9 protects against arbitrary detention or imprisonment. Some judges deem detention to be arbitrary if it is not authorized under statute, while others feel that detention is arbitrary whether authorized by statute or not if it be capricious or unreasonable. Finally, section 10 provides for certain rights to a person who is arrested or detained, such as the right to be informed of the reasons for arrest or detention, the right to be informed of his or her right to retain and instruct counsel and the right to do so, and the right to have the validity of the detention ascertained.